(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sinta D, Iskandar J, Gunawan B. 2022. Cultural strategies of the local and transmigrant communities in dealing with land and forest fire disasters in West Kotawaringin District, Central Kalimantan, Indonesia. Biodiversitas 23: 4705-4715. The Indonesian Province of Central Kalimantan has frequently faced catastrophic land and forest fire disasters in the last two decades. In 2015, the province experienced the most extensive land and forest fire disaster in Indonesia, causing severe ecological, economic, and socio-political problems. The villages of Baru and Kumpai Batu Bawah, located in South Arut Subdistrict, are included in the Priority Zone for Forest and Land Fire Disaster Management in West Kotawaringin District, Central Kalimantan Province, Indonesia. The two villages have been recognized as a high potential hazard and vulnerability to forest and land fires since 2015. This study aimed to compare the cultural strategies of the local communities of Baru Village with transmigrant communities of Kumpai Batu Bawah Village with distinctly different cultures in dealing with forest and land fires. The qualitative method was applied in this study. Several field techniques, including observation and semi-structured interviews or in-depth interviews with competent informants of local and transmigrant communities, were employed. The study showed that distinctive strategies were applied by two communities, based on the Traditional Ecological Knowledge (TEK) and embedded with culture for dealing with land and forest fire disasters in the Central Kalimantan ecosystem. Some TEK and cultural factors, including ways of looking at nature, and knowledge related to the environment expressed in the form of behavior such as land management practices for agriculture with disaster mitigation were documented as predominant factors of both communities for dealing with land and forest fire disasters.